Granular cell tumour (Abrikossoff's tumour): Case series - Sposto, Maria Regina [UNESP]; Navarro, Cláudia Maria [UNESP]; Andrade, Cleverton Roberto de [UNESP] (Elsevier, 2006)
This case series describes three unreported cases of an uncommon benign neoplasm named Abrikossoff's tumour or granular cell tumour (GCT). This mesenchymal neoplasm apparently arises from neural or Schwann cell origin with benign and malignant forms. All cases presented here were unique nodules on oral mucosa, coming out from the connective tissue, and occurring in women with age ranging from 30 to 42 years. The histological aspects of the GCT showed large granular cells arranged in groups and nests of connective tissue separating pseudoepitheliomatous overlying surface. This feature can possibly be misunderstood with squamous cell carcinoma. The differentiation between malignant and benign GCT is evaluated by the presence of metastases which is considered the only reliable criterion for malignancy. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Abrikossoff's tumour; Diagnosis; Granular cell tumour